A parallel algorithm for solving one problem of nonlinear optics - Čiegis, Raimondas; Kairytė, Genė; Ratė, P. (Lietuvos matematikos rinkinys, 1998)
This paper deals with a system of nonlinear differential equations, which describe the interaction of two focussed laser beams.The problem is approximated by a splitting finite difference scheme. A nonuniform and adaptive difference grid is used in the analysis. A parallel version of the finite-difference scheme is proposed and the efficiency of this algorithm is investigated.